Systemic Inhibition of Canonical Notch Signaling Results in Sustained Callus Inflammation and Alters Multiple Phases of Fracture Healing - Dishowitz, Michael I. (Public Library of Science, 2013)
The Notch signaling pathway is an important regulator of embryological bone development, and many aspects of development are recapitulated during bone repair. We have previously reported that Notch signaling components are upregulated during bone fracture healing. However, the significance of the Notch pathway in bone regeneration has not been described. Therefore, the objective of this study was to determine the importance of Notch signaling in regulating bone fracture healing by using a temporally controlled inducible transgenic mouse model (Mx1-Cre;dnMAML(f/-)) to impair RBPjκ-mediated canonical Notch signaling. The Mx1 promoter was synthetically activated resulting in temporally regulated systemic dnMAML expression just prior to creation of bilateral tibial fractures. This allowed for mice to undergo unaltered embryological and post-natal skeletal development. Results showed that systemic Notch inhibition prolonged expression of inflammatory cytokines and neutrophil cell inflammation, and reduced the proportion of cartilage formation within the callus at 10 days-post-fracture (dpf) Notch inhibition did not affect early bone formation at 10dpf, but significantly altered bone maturation and remodeling at 20dpf. Increased bone volume fraction in dnMAML fractures, which was due to a moderate decrease in callus size with no change in bone mass, coincided with increased trabecular thickness but decreased connectivity density, indicating that patterning of bone was altered. Notch inhibition decreased total osteogenic cell density, which was comprised of more osteocytes rather than osteoblasts. dnMAML also decreased osteoclast density, suggesting that osteoclast activity may also be important for altered fracture healing. It is likely that systemic Notch inhibition had both direct effects within cell types as well as indirect effects initiated by temporally upstream events in the fracture healing cascade. Surprisingly, Notch inhibition did not alter cell proliferation. In conclusion, our results demonstrate that the Notch signaling pathway is required for the proper temporal progression of events required for successful bone fracture healing.